1951
DOI: 10.1063/1.1748338
|View full text |Cite
|
Sign up to set email alerts
|

Near Ultraviolet Solution Spectra of the Diazines

Abstract: The near ultraviolet spectra of the diazines and various derivatives have been obtained in several solvents. Intensities, contours, and positions of the observed bands are combined with a valence-bond treatment of the diazine π-electrons to assign the transitions and to evaluate the C–C and C–N exchange integrals. The diazine band near 30,000 cm−1 (3333A) is assigned to a nonbonding nitrogen electron transition, and the band near 40,000 cm−1 (2500A) to a π-electron transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

1958
1958
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…In terms of symmetry, the ground state is designated as S 0 1 A g of the D 2h point group, and the lowest singlet np* and pp* excited states have conventionally been assigned as S 1 1 B 3u and S 2 1 B 2u , respectively. The details in the ultraviolet absorption spectra of pyrazine were first resolved in solution in 1950s, [1] and the data from vapors were obtained in the following decades. [2][3][4][5][6][7] People found that the 325 nm absorption band, that is, the np* 1 B 3u state, has a lot of sharp peaks that have been assigned as n 6a (a g ), n 9a (a g ), n 10a (b 1g ) fundamentals and their overtones as well as combination bands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of symmetry, the ground state is designated as S 0 1 A g of the D 2h point group, and the lowest singlet np* and pp* excited states have conventionally been assigned as S 1 1 B 3u and S 2 1 B 2u , respectively. The details in the ultraviolet absorption spectra of pyrazine were first resolved in solution in 1950s, [1] and the data from vapors were obtained in the following decades. [2][3][4][5][6][7] People found that the 325 nm absorption band, that is, the np* 1 B 3u state, has a lot of sharp peaks that have been assigned as n 6a (a g ), n 9a (a g ), n 10a (b 1g ) fundamentals and their overtones as well as combination bands.…”
Section: Introductionmentioning
confidence: 99%
“…Domcke and co-workers firstly carried out ab initio calculations combined with mathematical models to describe this internal conver-Abstract: The geometric, energetic, and spectroscopic properties of the ground state and the lowest four singlet excited states of pyrazine have been studied by using DFT/TD-DFT, CASSCF, CASPT2, and related quantum chemical calculations. The second singlet np* state, 1 A u , which is conventionally regarded dark due to the dipole-forbidden 1 A u ! 1 A g transition, has been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The features of the spectra of vinylpyridines are not similar to that of pyridine [14]; this dissimilarity indicates that the molecule is a rigid planar one and not a free rotator. Consequently, the extension of conjugation is pronounced and the ortho-ortho hydrogen steric effect is negligible.…”
Section: A Vinylpyridinesmentioning
confidence: 77%
“…The spectra of five representative quaternary compounds (3, 6, II, 14 and 16) lack the distinct 215 nm band, which is replaced by a rather broad shoulder (e -3280) centered at the same place. The appearance of such a shoulder may be related to a certain shift due to the newly formed C -N bond, reflecting a reduced delocalization of the electron pair [7]. No change in the 250 nm band was detected.…”
mentioning
confidence: 92%